Comparative Analysis of Results Between Robot-Assisted and Open Radical Prostatectomy - Nikolay Kolev (Journal of Biomedical & Clinical Research, 2019)
We aimed to compare results between patients with early- stage prostate cancer who underwent robot-assisted and open radical prostatectomy. We examined preoperative and postoperative data, early and late complications, and analysed oncological and functional outcomes (continence and erectile function) during follow-up.We studied the data of 123 patients with localized prostate cancer, operated with nerve-sparing retropubic radical prostatectomy, divided into two groups. Group 1 included 70 patients who underwent robot-assisted radical prostatectomy (RARP). Group 2 included 53 patients, on whom open retropubic radical prostatectomy (RRP) was performed. We compared preoperative data, complications rate, oncological, and functional outcome (continence and erectile function) during the follow-up period.Operative time was significantly lower in the RRP group. Blood loss and earlier removal of the urinary catheter were significantly lower in the RARP group. The percentage of significant postoperative complications (Clavien-Dindo III-IV) was 0% in the first group and 3% in the second group. During follow-up, the improvement in the functional outcome - continence and erectile function was significantly better in the robot-assisted surgery patients.There were statistically significant better functional outcomes in patients operated on using the robot-assisted technique. The operating time was shorter in the classic radical prostatectomy. The application of robot-assisted radical prostatectomy may help achieve earlier recovery, as compared to open radical prostatectomy.